Стража! Стража!: [фантастический роман] / Терри Пратчетт - Пратчетт Терри (ЭКСМО, 2007)
Экземпляры: ф.2 (20171013) / Инвентарный номер: 57719 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: П 70 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-445